1997
DOI: 10.4028/www.scientific.net/msf.258-263.1795
|View full text |Cite
|
Sign up to set email alerts
|

Rate Limiting Mechanism of Transition Metal Gettering in Multicrystalline Silicon

Abstract: We have performed studies on multicrystalline silicon used for solar cells in the as-grown state and after a series of processing and gettering steps. The principal goal of this work is to determine the rate limiting step for metal impurity gettering from multicrystalline silicon with an emphasis on the release of impurities from structural defects. Synchrotron-based x-ray fluorescence mapping was used to monitor the release process. Copper and nickel impurities were found to reside primarily at dislocations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…But up to now, few papers have been published about copper precipitation in cast multicrystalline silicon (mc-Si) [19,20]. Moeller et al [19] observed with TEM the micro-feature of copper precipitates in mc-Si and found that copper nucleated preferentially at dislocations and at steps of grain boundaries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But up to now, few papers have been published about copper precipitation in cast multicrystalline silicon (mc-Si) [19,20]. Moeller et al [19] observed with TEM the micro-feature of copper precipitates in mc-Si and found that copper nucleated preferentially at dislocations and at steps of grain boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Moeller et al [19] observed with TEM the micro-feature of copper precipitates in mc-Si and found that copper nucleated preferentially at dislocations and at steps of grain boundaries. McHugo et al [20] mainly studied the gettering effect of copper in mc-Si. However, the influence of annealing temperature and cooling rate on copper precipitation in mc-Si is still unclear.…”
Section: Introductionmentioning
confidence: 99%